ANALISIS FAKTOR YANG MEMPENGARUHI KONSUMSI RUMAH TANGGA PELAKU USAHA PANDAI BESI DI KELURAHAN MASSEPE KABUPATEN SIDENRENG RAPPANG - Bahruddin, Bahruddin; Agusriani, Uci (Cateris Paribus Journal, 2021)
The issue raised in this study is whether income factors, and the number of family dependents have a significant effect on the consumption of blacksmith households in Massepe Village of Sidenreng Rappang Regency. The variables observed in this study are household consumption (Y), income (X1), number of family dependents (X2). The type of research used is a type of quantitative research. Where the data used in the form of primary data will be obtained through questionnaires and in analysis with linear regression analysis techniques multiple with spss application program tools version 24 to analyze factors that affect the consumption of blacksmith households in Massepe Village in Sidenreng Rappang Regency. The results of this study showed that income, and the number of family dependents had apositive and significant effect on the consumption of blacksmith households in Massepe village di Sidenreng Rappang Regency.